Why Legislators are Protectionists: The Role of Majoritarian Voting in Setting Tariffs - Gerald Willmann (Kiel University, Department of Economics, 2003)
Based on the observation that industries are often geographically concentrated, this paper proposes a new political economy model of trade protection. We associate the sectors of a specific factors model with electoral districts populated by continua of heterogeneous voters who differ in their relative factor endowments. We show how strategic delegation leads each district to elect a representative who is more protectionist than the median voter. The legislature formed by these representatives then sets tariffs that are strictly positive. Introducing additional policy instruments reveals a trade-off between efficiency and regional targetability.
urn:nbn:de:101:1-200911022624
Keywords: D72; F10; F13; 330; trade policy; political economy; representative democracy; Protektionismus; Zollpolitik; Mehr-Sektoren-Modell; Wahlkreis; Ökonomische Theorie der Demokratie; Abstimmungsregel; Theorie